จีนในทัศนะของทหารไทย: ภาพสะท้อนจากเอกสารวิจัยวิทยาลัยป้องกันราชอาณาจักร - รชยา เทียมประชา (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This Thesis aims to study Sino-Thai relations from Thai Military Perspectives after Coup in 2006 and 2014 because this period is considered the Military’s intervention in Thai Politics. To understand the Thai Military perspectives that reflect from the National Defense College Research Paper, there are 4 perspectives that are summarized from Sino-Thai relations 1) China on Thai right-wing conservative view 2) China is a threat 3) China on ASEAN’s perspective, and 4) Sino-Thai special relationship. This thesis finds that the National Defense College Research Paper can be grouped according to their contents to match with each of 4 perspectives above: Perspective 1 has got a total of 2 research papers (11%), Perspective 2 China as a Threat has got a total of 1 research paper (6%), Perspective 3 has got a total of 6 research paper (33%), and Perspective 4 has got a total of 9 research papers (50%). To conclude, China in Thai Military Perspectives is likely to continue its relationship with China based on Sino-Thai special relationship and ASEAN’s views.